RICA 2020
DOI: 10.20937/rica.53711
|View full text |Cite
|
Sign up to set email alerts
|

PATOTIPOS Y RESISTENCIA A ANTIBIÓTICOS DE Escherichia coli EN AGUA RESIDUAL

Abstract: Palabras clave: efluente, resistencia bacteriana, agua residual. RESUMENLa contaminación del agua es un problema ambiental grave. En una planta de tratamiento de agua residual (PTAR) en México se evaluó la presencia de coliformes fecales totales y de Escherichia coli, la prevalencia de patotipos diarreicos y los perfiles de resistencia a los antibióticos en las diferentes etapas del tratamiento. Se realizaron tres muestreos compuestos para evaluar la presencia de E. coli con los parámetros físicos y químicos e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…According to the studies carried out by Martínez-Orgániz et al [34] and Martínez-Orgániz et al [69], the "Aguas Blancas" treatment plant complies with the requirements established according to Mexican Standards. The research proposes a modification in the treatment process to avoid the presence of various types of emerging contaminants, and microorganisms such as E. coli.…”
Section: Proposal For the Reuse Of Treated Water: Acapulco Study Casementioning
confidence: 88%
“…According to the studies carried out by Martínez-Orgániz et al [34] and Martínez-Orgániz et al [69], the "Aguas Blancas" treatment plant complies with the requirements established according to Mexican Standards. The research proposes a modification in the treatment process to avoid the presence of various types of emerging contaminants, and microorganisms such as E. coli.…”
Section: Proposal For the Reuse Of Treated Water: Acapulco Study Casementioning
confidence: 88%
“…Several studies have identified antibiotic-resistant and pathogenic E. coli strains in environmental water samples from Mexico [ 13 , 14 , 15 , 16 , 17 ]. Previous studies in Sinaloa, Mexico, have reported E. coli as a major biological pollutant of diverse aquatic resources, including agricultural drainage, drinking, and irrigation water [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%